2004
DOI: 10.1099/mic.0.27330-0
|View full text |Cite
|
Sign up to set email alerts
|

A virulence-associated gene microarray: a tool for investigation of the evolution and pathogenic potential of Staphylococcus aureus

Abstract: An oligonucleotide probe microarray for investigation of the evolution of epidemic Staphylococcus aureus strains has been constructed. The array comprises 383 probes based on virulence-associated genes present in four key strains. Twelve strains including seven for which the complete chromosomal nucleotide sequence was available were tested on the array. Twenty-six per cent of the probes were able to differentiate between strains to give a minimum of two gene differences between pairs. A gene difference distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Several studies have examined the presence of both mobile and stable genetic determinants of the staphylococcal virulon (2,33,34,41,50). From this analysis, along with the seven publicly available genomes and recent DNA microarray comparisons (3,8,45,52), it is apparent that most elements are not exclusively associated with one agr type-though there may be considerable variations in the frequency of carriage of these elements. This is clearly evident in a set of 198 isolates previously characterized by Jarraud et al using amplified fragment length polymorphism, where it was shown that these elements are found in multiple agr groups at different frequencies-and that some combinations of these elements are frequently found together or apart (20).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the presence of both mobile and stable genetic determinants of the staphylococcal virulon (2,33,34,41,50). From this analysis, along with the seven publicly available genomes and recent DNA microarray comparisons (3,8,45,52), it is apparent that most elements are not exclusively associated with one agr type-though there may be considerable variations in the frequency of carriage of these elements. This is clearly evident in a set of 198 isolates previously characterized by Jarraud et al using amplified fragment length polymorphism, where it was shown that these elements are found in multiple agr groups at different frequencies-and that some combinations of these elements are frequently found together or apart (20).…”
Section: Discussionmentioning
confidence: 99%
“…While these DNA microarray systems provide a large amount of information about the isolate's genome, their use is restricted mainly to specialized research laboratories, as data analysis is complicated (29,50,52,56). In contrast, several groups have recently developed more focused DNA microarrays (12,35,36,43), with one system in particular offering simultaneous highthroughput genotyping of S. aureus isolates by assigning isolates to an MLST clonal complex (CC) or ST and to an SCCmec type and detection of species-specific markers, accessory gene regulator (agr) alleles, capsule types, MSCRAMMs, and a range of clinically relevant antimicrobial resistance and virulence-associated genes (34)(35)(36).…”
mentioning
confidence: 99%
“…Indeed, Fitzgerald et al used a microarray composed of approximately 92% of the S. aureus strain COL genome (2,817 open reading frames [ORFs]) to screen 36 clinical S. aureus isolates and found that 22% of the COL genome was missing in at least 1 of the test isolates (13). S. aureus microarrays with a subset of known virulence genes have also been described (27,37) and highlight substantial variation between isolates. For other bacteria, including Bordetella spp.…”
mentioning
confidence: 99%